Visualizing Functional Emotions: Mapping Counseling Responses from Text to Virtual Facial Expressions - Rifki Padilah; Rifki Wijaya; Shaufiah (Telkom University, 2025)
This research develops an innovative virtual counseling system by integrating text-based emotion classification with visual representation to address the problem of early marriage in Lombok. The system leverages the sophisticated IndoRoBERTa model to accurately classify conselor responses into five functional emotion categories relevant to the counseling context: Enthusiasm, Gentleness, Analytical, Inspirational, and Cautionary. The limitations of conventional counseling services in rural areas serve as the primary justification for developing this responsive and accessible technological solution. Evaluation results demonstrate that the IndoRoBERTa model achieves a highly competitive accuracy rate of 89% after being trained on an expanded dataset, an achievement that significantly surpasses previous architectures. In conclusion, this IndoRoBERTa-based system is not only technically viable but also effective as a tool for providing initial empathetic support. Its capability to translate textual emotions into non-verbal visual cues makes it a promising technological solution to bridge the gap in current counseling services.